Highly enhanced thermal conductivity of epoxy composites by constructing dense thermal conductive network with combination of alumina and carbon nanotubes. (October 2019) - Yan, Rong; Su, Fan; Zhang, Ling; Li, Chunzhong
Graphical abstract: The construction of heat transfer path and thermal conductivity of different composites. Abstract: Achieving highly out-plane TC composites by building thermal conductive network at possible low content of conductive fillers is crucial and urgent to realize miniaturization, integration, and high-power density of electronic devices. In this study, highly thermal conductive composites based on pre-selected size of micro-Al2 O3 (20 μm and 70 μm), acidified MWCNTs and silica nanoparticles (SiO2 NPs) are fabricated via a facile mixing process. Enhanced thermal conductive network was constructed by small functionalized Al2 O3 (f-Al2 O3 ) particles gap filling between large f-Al2 O3 particles and the MWCNTs connection with adjacent f-Al2 O3 particles. SiO2 NPs are used to avoid the sedimentation of f-Al2 O3 particles and improve the dispersion of MWCNTs. The obtained composites show very high out-plane TC (1.73 W·m −1 ·K −1 ) at only 60 wt% Al2 O3 (20 μm/70 μm: mass fraction, 1/3), 3 wt% MWCNTs and 8 wt% SiO2 . It is attributed to the synergistic effect of different size of f-Al2 O3 and the MWCNTs to form the dense thermal conduction path. The high out-plane TC and low electric conductivity provide this material great potential as candidate for heat dissipation parts in electronic devices.